2015
DOI: 10.20286/nova-jmbs-040245
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of Syzygium cumini leave extracts against selected microorganisms

Abstract: Leaves extracts of Syzygium cumini (L) were collected to test their antimicrobial activity. The collected materials were extracted by petroleum ether, methanol and water by using different concentration (15% 10% and 5%). Were obtained and bioassay in vitro for its bioactivity to inhabit the growth of four types of bacteria,namely; (Staphlococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Bacillus subitils) and two types of fungi (Aspergillus niger, and Candida albicans). The extract of Syzygium cumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, methanol extracts exerted inhibition against E. coli (18 mm), B. subtilis (20 mm), S. aureus (15 mm), P. aeruginosa (18 mm) at MIC of 15 %. [45] Also, the antimicrobial activity of Jamun fruit and leaf extracts was investigated against various bacterial strains such as E. coli, Proteus vulgaris, Pseudomonas aeruginosa, Raoultella planticola, S. aureus, Staphylococcus saprophyticus, including several fungal strains of Candida albicans (MTCC 183), Aspergillus niger (MTCC 282), Fusarium solani (MTCC 9667) and Penicillium chrysogenum (MTCC 161) by filter paper disc method. A potential antimicrobial activity at a dose of 20 mg/10 mL was seen in case of chloroform extract owing to the presence of maximum phytoconstituents in this extract.…”
Section: Antibacterial and Antiviral Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, methanol extracts exerted inhibition against E. coli (18 mm), B. subtilis (20 mm), S. aureus (15 mm), P. aeruginosa (18 mm) at MIC of 15 %. [45] Also, the antimicrobial activity of Jamun fruit and leaf extracts was investigated against various bacterial strains such as E. coli, Proteus vulgaris, Pseudomonas aeruginosa, Raoultella planticola, S. aureus, Staphylococcus saprophyticus, including several fungal strains of Candida albicans (MTCC 183), Aspergillus niger (MTCC 282), Fusarium solani (MTCC 9667) and Penicillium chrysogenum (MTCC 161) by filter paper disc method. A potential antimicrobial activity at a dose of 20 mg/10 mL was seen in case of chloroform extract owing to the presence of maximum phytoconstituents in this extract.…”
Section: Antibacterial and Antiviral Activitiesmentioning
confidence: 99%
“…Petroleum ether and methanol extract of JLs were tested by cup‐plate agar diffusion method for observing the subsequent activity of gram‐positive ( S. aureus (ATCC/25923) and Bacillus subtilis (NCTC/8236)) and two gram‐negative bacteria ( Pseudomonas aeruginosa (ATCC/27853) and E. coli (ATCC/25922), including two fungal species ( Candida albicans (ATCC/7596) and Aspergillus niger ATCC/9763 and petroleum ether extracts showed the inhibitory activity (18 mm) against E. coli at MIC of 10 % and as well as at 15 %. However, methanol extracts exerted inhibition against E. coli (18 mm), B. subtilis (20 mm), S. aureus (15 mm), P. aeruginosa (18 mm) at MIC of 15 % [45] . Also, the antimicrobial activity of Jamun fruit and leaf extracts was investigated against various bacterial strains such as E. coli, Proteus vulgaris, Pseudomonas aeruginosa, Raoultella planticola, S. aureus, Staphylococcus saprophyticus , including several fungal strains of Candida albicans (MTCC 183), Aspergillus niger (MTCC 282), Fusarium solani (MTCC 9667) and Penicillium chrysogenum (MTCC 161) by filter paper disc method.…”
Section: Biological Properties Of S Cumini Leavesmentioning
confidence: 99%
“…Hasanuzzaman et al [13] performed phytochemical screening of methanolic, acetone, chloroform and n-hexane extracts of S. cumini seeds, root, stem, bark, leaves. The antimicrobial potential of methanolic, aqueous, and petroleum ether extracts of S. cumini leaves was tested by Elfadil et al [14] against bacteria (viz. Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subitlis) and fungi (Aspergillus niger and Candida albicans).…”
Section: Kingdommentioning
confidence: 99%
“…He suggested that further research work should be carried out on this plant to determine the toxicity as well as the optimum dose. The result should then be compared with standard antibiotics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%